PROFIL FAKTOR RISIKO YANG BERHUBUNGAN PADA NYERI KEPALA PRIMER - Wahyuliati, Tri; Ardiyanto, Rizky (Universitas Tadulako, 2024)
Headache is a common patient complaint in the world with prevalence in the adult population is 50%. Headache can be divided into two types based on their causes. They are primary headaches and secondary headaches. The examples of primary headaches are migraine, Tension Type Headaches (TTH), and cluster headaches. The background indicates that this research needs to be carried out to determine the profile of risk factors associated with primary headache. An analytic observational study with a cross-sectional design conducted at the Temanggung Hospital. The subjects of this study were patients at the neuro polyclinic for the period 1 September 2019 to 30 September 2021, with a total of 88 subjects. The data were analyzed using the chi-square test. The distribution of primary headaches was migraine (19.3%), TTH (64.1%), and cluster headaches (15.9%). The results of Chi-square test between risk factors and primary headache found that age (p = 0.02), gender (p = 0.816), BMI (p = 0.223), smoking history (p = 0.166) family history with headache (p = 0.035), and stress (p = 0.022). Age, family history with headache, and stress have relationship with primary headache, while gender, BMI, and smoking history haven’t relationship with primary headache.